2020
DOI: 10.3390/nu12051300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arginine Supplementation on Athletic Performance Based on Energy Metabolism: A Systematic Review and Meta-Analysis

Abstract: Nitric oxide related ergogenic aids such as arginine (Arg) have shown to impact positively on sport performance through several physiological and metabolic mechanisms. However, research results have shown to be controversial. The great differences regarding required metabolic pathways and physiological demands between aerobic and anaerobic sport disciplines could be the reasons. The aim of this systematic review and meta-analysis was to evaluate the effects of Arg supplementation on aerobic (≤VO2max) and anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 68 publications
0
52
3
Order By: Relevance
“…In the realm of sports science, majority of studies focused on the change of exercise performance and anthropometric change following the oral supplementation of glutamine and arginine [ 58 , 59 ]. Therefore, as a benefit in return, how the exercise types, intensities, or duration determine the waxing and waning of metabolic profiles needs to be verified as Oov Pilates program in our study led to the change of specific metabolites associated with short-term and moderate exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of sports science, majority of studies focused on the change of exercise performance and anthropometric change following the oral supplementation of glutamine and arginine [ 58 , 59 ]. Therefore, as a benefit in return, how the exercise types, intensities, or duration determine the waxing and waning of metabolic profiles needs to be verified as Oov Pilates program in our study led to the change of specific metabolites associated with short-term and moderate exercise intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different L-arginine dosages used in chronic and acute supplementation protocols could have different physiological mechanisms of action. A recent meta-analysis reported that the effective dose of LAS should be adjusted to 0.15 g/kg body weight taken 60-90 min before exercise in the acute protocol or 10-12 g LAS for 8 weeks in chronic protocol for improving both aerobic and anaerobic performances (Viribay et al, 2020).…”
Section: Includedmentioning
confidence: 99%
“…On the other hand, NO synthase-dependent pathway supplements, such as arginine or citrulline, have shown different results. While arginine supplementation has demonstrated improvements in both aerobic and anaerobic performance with acute (0.15 g/kg) or chronic (1.5-2.0 g/day for 4-7 weeks or 10-12 g/day for 8 weeks) protocols [61], acute protocols of citrulline supplementation (3-6 g) showed a small effect size (0.2) on high-intensity strength and power performance in resistance exercise [62]. In master female tennis players (51.0 ± 9.0 years), acute protocol with 8 g of citrulline improved handgrip strength and power peak in a specific anaerobic test, but not the capacity of sustained power or jump power [37].…”
Section: Effects Of Nitric Oxide (No) Precursors In Racquet Sportsmentioning
confidence: 99%